INTERCONNECTION OF EPD AND PDM ENVIRONMENTS IN INSTRUCTION - Jiří, MAXA; NEDĚLA, Vilém (Trends in education, 2008)
The world trend TPV tends complex solutions of the system from the from of a sketch to manufacture. In order to be prepared for this trend, the Universities are required to react to it. There is a system of courses described in the article which in forms the students about this methodology.
Keywords: CAx; EPD; PDM; PLM